2018
DOI: 10.1039/c8nj03339k
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-activated C–C and C–N bond formation in the synthesis of imidazo[1,2-a]pyridines and imidazo[2,1-b]thiazoles under catalyst and solvent-free conditions

Abstract: Synthesis of 3-aminoimidazo-fused heterocycles via the Groebke–Blackburn–Bienaymé reaction using a universally available energy source under catalyst and solvent-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…[56] Shivhare et al reported a suitable synthetic methodology for the synthesis of imidazo[1,2-a]pyridine (59 a) and imidazo [2,1-b]thiazole (59 b) derivatives using aromatic aldehydes (56), isocyanides (57) and 2-aminoheterocycles (58 a, 58 b) under visible light irradiation (24 W CFL) without the use of any solvent or catalyst (Scheme 29). [57] When this reaction was performed in the absence of light, only a trace amount of product was obtained. After screening different intensities of visible light, 24 W CFL was found to be the best light source for this transformation giving 97 % yields of products.…”
Section: Synthesis Of Imidazo-fused Derivativesmentioning
confidence: 99%
“…[56] Shivhare et al reported a suitable synthetic methodology for the synthesis of imidazo[1,2-a]pyridine (59 a) and imidazo [2,1-b]thiazole (59 b) derivatives using aromatic aldehydes (56), isocyanides (57) and 2-aminoheterocycles (58 a, 58 b) under visible light irradiation (24 W CFL) without the use of any solvent or catalyst (Scheme 29). [57] When this reaction was performed in the absence of light, only a trace amount of product was obtained. After screening different intensities of visible light, 24 W CFL was found to be the best light source for this transformation giving 97 % yields of products.…”
Section: Synthesis Of Imidazo-fused Derivativesmentioning
confidence: 99%
“… Photocatalytic synthesis of imidazol pyridines and imidazol thiazoles under solvent-free conditions. The yellow bulb-shaped sign indicates irradiation with visible light [ 145 ]. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…In the year 2018, Siddiqui and collaborators described a photocatalyzed methodology for the synthesis of imidazole pyridines and imidazole thiazoles under solvent-free conditions and without the need for a catalyst, using only visible light as an activator (Scheme 19) [145]. Scheme 19.…”
Section: Photocatalysis Under Solvent-free Conditionsmentioning
confidence: 99%
“…Synthesis of imidazo[2,1-b]thiazole benzimidazole conjugates (57) as microtubule-targeting agents was developed by Baig et al [31] Here, the oxidative cyclization of . [43] Imidazo[2,1-b] thiazoles bearing 1,2,3-triazole have good pharmacological properties such as anticancer [44,45] anti-inflammatory [43] and antimicrobial [46] activities.…”
Section: M Afsina Abdulla Was Born Inmentioning
confidence: 99%
“…Imidazothiazoles and its derivatives are synthesized by a plethora of reactions involving multicomponent reactions (MCRs), [24][25] biosynthesis of staphyloxanthin produced by staphylococcus aurease in the presence of dehydrosqualene synthase enzyme, [27] transition metal catalysed reactions, [28] visible light synthesis, [29] regioselective reaction, [30] Groebke-Blackburn-Bienayme-Reaction (GBBR) mechanism, [24,31] oxidative cyclisation, [32] Claisen-Schmidt condensation, [33] microwave assisted green synthesis [34] and ring-opening and ring-closing reconstruction reactions. [35] Multi-component reactions are reactions involving a combination of three or more substrates, which are carried out in a one-pot system to obtain the desired product.…”
Section: Introductionmentioning
confidence: 99%